It Takes Two to Tango: Combining Conventional Culture With Molecular Diagnostics Enhances Accuracy of Streptococcus pneumoniae Detection and Pneumococcal Serogroup/Serotype Determination in Carriage - Miellet, Willem R.; van Veldhuizen, Janieke; Litt, David; Mariman, Rob; Wijmenga-Monsuur, Alienke J.; Badoux, Paul; Nieuwenhuijsen, Tessa; Thombre, Rebecca; Mayet, Sanaa; Eletu, Seyi; Sheppard, Carmen; van Houten, Marianne Alice; et al. (Frontiers in Microbiology, 2022)
ABSTRACT Background: The specificity of molecular methods for the detection of Streptococcus pneumoniae carriage is under debate. We propose a procedure for carriage surveillance and vaccine impact studies that increases the accuracy of molecular detection of live pneumococci in polymicrobial respiratory samples. Methods: Culture and qPCR methods were applied to detect pneumococcus and pneumococcal serotypes in 1549 nasopharyngeal samples collected in the Netherlands (n=972) and England (n=577) from 946 toddlers and 603 adults, and in paired oropharyngeal samples collected exclusively from 319 Dutch adults. Samples with no live pneumococci isolated at primary diagnostic culture yet generating signal specific for pneumococcus in qPCRs were re-examined with a second, qPCR-guided culture. Optimal Cq cut-offs for positivity in qPCRs were determined via receiver operating characteristic (ROC) curve analysis using isolation of live pneumococci from the primary and qPCR-guided cultures as reference. Results: Detection of pneumococcus and pneumococcal serotypes with qPCRs in cultured (culture-enriched) nasopharyngeal samples exhibited near-perfect agreement with conventional culture (Cohen’s kappa: 0.95). Molecular methods displayed increased sensitivity of detection for multiple serotype carriage, and implementation of qPCR-guided culturing significantly increased the proportion of nasopharyngeal and oropharyngeal samples from which live pneumococcus was recovered (p<0.0001). For paired nasopharyngeal and oropharyngeal samples from adults none of the methods applied to a single sample type exhibited good agreement with results for primary and qPCR-guided nasopharyngeal and oropharyngeal cultures combined (Cohens kappa; 0.13 to 0.55). However, molecular detection of pneumococcus displayed increased sensitivity with culture-enriched oropharyngeal samples when compared with either nasopharyngeal or oropharyngeal primary cultures (p<0.05). Conclusions: The accuracy of pneumococcal carriage surveillance can be greatly improved by complementing conventional culture with qPCR and vice versa, by using results of conventional and qPCR-guided cultures to interpret qPCR data. The specificity of molecular methods for the detection of live pneumococci can be enhanced by incorporating statistical procedures based on ROC curve analysis. The procedure we propose for future carriage surveillance and vaccine impact studies improves detection of pneumococcal carriage in adults in particular and enhances the specificity of serotype carriage detection.